The Stakeholders’ Collaborative Toward the Community Empowerment Based on Village Tourism in the Melung Village - Indah Ayu Permana Pribadi; Dian Nastiti (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
Melung Village have collaborated with BUMDes Melung to develop the Pagubugan tourist attraction as the initiation of Melung Tourism Village. Currently, Melung Village is expanding to other tourism sectors such as cultural tourism, culinary tourism, and educational tourism. This research was conducted to see how stakeholder collaboration in the process of community empowerment based on tourism villages in Melung Village. This research used a qualitative case study approach. Key informants in this study were the Head of Melung Village and related stakeholders. The results of this study explain that collaboration among stakeholders in community empowerment based on tourism villages in Melung Village, Kedungbanteng sub-district has been running well despite some obstacles such as the lack of community participation. In this regard, related stakeholders continue to make efforts to improve community participation by conducting various training to support the development of Melung Tourism Village.